Infância, consumo e educação: conexões e diálogos - Brites Albertini, Marcelize Niviadonski (2016)
The growing process of industrialization and commercialization has embroiled the consumerist logic in different social groups including even children, since the discovery of its potential consumer awakened commercial interests in various segments. From this context, this paper supported on a theoretical study in which bibliographic and documentary analysis would establish connections between the triad: childhood, consumption and education, by seeking to reflect and talk about this relationship in today's contemporary society. At first we intend to know the evolution of the concept of childhood over time, their cultural historical context, as well as to understand this concept today. Later we will present considerations about the dilemmas of contemporary childhood and observations about the influence of consumer culture, and further on we will seek opportunities in education paths for understanding and reflecting upon the analysis of consumerist logic. Perspectives brought to light by this study suggest that thinking and rethinking childhood in the consumer culture must become axis of the major themes in school’s education process, because education can provide mediation to foster an analytical and reflective look forward to the consumerist logic, stimulating, thus, significant changes in children's behavior as consumers.